Yoga Anak untuk Pola Nafas dan Aktifitas Jasmani - Diah Ayu Maharani; Heni Hirawati Pranoto; Pinky Aprilya; Isri Nasifah (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
Children absorb and process information through movement, seeing, hearing, touching and also singing. Using all these activities can help improve aspects of children's development (Wening, 2003). These aspects of growth and development include: aspects of religious and moral values, physical-motor aspects, cognitive aspects, language aspects, social-emotional aspects, and artistic aspects (Kemendikbud.2014). This community service activity is carried out through direct counseling in Kemawi village, carried out in several stages, namely children's yoga practice, licensing to the village midwife, implementation of activities for preschool children. Children's yoga movements can help children's physical strength, from muscles, bones to gross motor mobility and flexibility. This community service activity is carried out through direct counseling in Kemawi Village, precisely at the Bunga Harapan Kindergarten. The participants in this activity were 34 preschool children. All children do yoga well. Children can follow instructions from training even though they are not perfect.   Abstrak Anak menyerap dan mengolah informasi melalui gerakan, melihat, mendengar, menyentuh dan juga mennyanyi. Mempergunakan seluruh kegiatan tersebut dapat membantu meningkatkan aspek perkembangan anak (Wening,2003). Aspek pertumbuhan dan perkembangan tersebut meliputi : aspek nilai agama dan moral, aspek fisik-motorik, aspek kognitif, aspek bahasa, aspek sosial-emosional, serta aspek seni(Kemendikbud.2014). Kegiatan pengabdian masyarakat ini dilakukan melalui penyuluhan langsung di desa Kemawi dilaksanakan beberapa tahapan yaitu latihan yoga anak, perizinan kepada bidan desa, pelaksanaan kegiatan pada anak prasekolah. Gerakan –gerakan   yoga anak dapat   membantu kekuatan fisik anak, dari otot, tulang hingga mobilitas gerak motorikkasar dan fleksibilitasnya. Kegiatan Pengabdian masyarakat ini dilakukan melalui penyuluhan langsung di Desa Kemawi tepatnya di Taman Kanak-Kanak Bunga Harapan. Peserta dalam kegiatan ini   berjumlah   34 anak prasekolah. Semua anak melakukan yoga dengan baik. Anak dapat mengikuti instruksi dari pengapdian meskipun belum sempurna.